Racial Differences in Prevalence and Clinical Characteristics of Asthma–Chronic Obstructive Pulmonary Disease Overlap - Jo, Yong Suk; Hwang, Yong Il; Yoo, Kwang Ha; Lee, Myung Goo; Jung, Ki Suck; Shin, Kyeong-Cheol; Yoon, Hyoung Kyu; Kim, Deog Kyeom; Lee, Sang Yeub; Rhee, Chin Kook (Frontiers in Medicine, 2021)
Background: This study examined the differences in prevalence and clinical features of asthma–chronic obstructive pulmonary disease (COPD) overlap (ACO) with identical diagnostic criteria by race and ethnicity in two nationwide cohorts of COPD. Methods: We used data from the Korean COPD Subgroup Study (KOCOSS) and phase I of the US Genetic Epidemiology of COPD (COPDGene) study. We defined ACO by satisfying bronchodilator response (BDR) >15% and 400 mL and/or blood eosinophil count ≥300/μL. Results: The prevalences of ACO according to ethnicity were non-Hispanic white (NHW), 21.4%; African American (AA), 17.4%; and Asian, 23.8%. Asian ACO patients were older, predominantly male, with fewer symptoms, more severe airflow limitation, and fewer comorbidities than NHW and AA patients. During 1-year follow up, exacerbations occurred in 28.2%, 22.0%, and 48.4% of NHW, AA, and Asian ACO patients, respectively. Compared to non-ACO patients from the same racial group, risk for exacerbation was significantly higher in NHW and Asian ACO patients (adjusted incident rate ratio [aIRR], 1.17; 95% confidence interval [CI], 1.01–1.36, and aIRR, 1.37; 95% CI, 1.09–1.71 for NHW and Asian ACO patients, respectively). Inhaled corticosteroid (ICS) reduced the risk for future exacerbation in total ACO patients but the effect was not significant in each racial groups. Conclusions: The prevalence of ACO was similar in two cohorts using the same diagnostic criteria. The risk for future exacerbation was significantly higher in ACO, and the use of ICS reduced the risk for exacerbation in total ACO patients.